Thermal and Morphology Studied of PVC-PS Blends - R. Vijayalakshmi Rao, Mrs.; Ashokan, P.V. (Asian Journal of Chemistry, 2012)
Thermal properties and morphology of blends of polyvinyl chloride (PVC) and polystyrene (PS) prepared by three mixing techniques namely solution casting, precipitation of solution by non-solvent and melt extrusion have been studied over a wide range of compositions. It was observed that the glass transition temperature (Tg), melting point (Tm) and enthalpy change at melting (∆H) and Cp were influenced by the composition of the blends and also Tg, Tm and ∆H were altered from their theoretical values.